واقع التحضير النفسي لدى الفئات العمرية من 15 الى 17 سنة بنوادي كرة القدم - كساسوية يزيد (My University, 2024)
ملخص :  عنـوان الدراسـة:واقع التحضير النفسي لدى الفئات العمرية من 15 الى 17 سنة بنوادي كرة القدم  هـدف الدراسـة: − التعرف على ما ان كانت نوادي كرة القدم تستخدم الإعداد النفسي للاعب في التغلب على بعض المواقف السلبية. − تحديد مدى استخدام نوادي كرة القدم الإعداد النفسي للاعب على الاسترخاء والهدوء عقب المسابقات. − تبيين درجة استخدام نوادي كرة القدم الإعداد النفسي للاعب على تنمية وتطوير صفاته الشخصية.  فرضـيات الدراسـة: − تستخدم نوادي كرة القدم الإعداد النفسي للاعب في التغلب على بعض المواقف السلبية. − تستخدم نوادي كرة القدم الإعداد النفسي للاعب على الاسترخاء والهدوء عقب المسابقات. − تستخدم نوادي كرة القدم الإعداد النفسي للاعب على تنمية وتطوير صفاته الشخصية.  إجـراءات الدراسـة الميدانيـة: − العينـة: تمتالدراسة على عينة قوامها 62 لاعب من نوادي كرة القدم على مستوى الرابطة الولائية سوق اهراس. − المجـال الـزماني: تم إجراء الدراسة الأساسية في الفترة الممتدة من 20/01/2024 إلى غاية 10/05/2024. − المجال المكاني: تمت الدراسة على مستوى النوادي الرياضية التابعين للرابطة الولائية لكرة القدم - سوق أهراس.  المنهـج المستخـــدم: تم استخدام المنهج الوصفي المسحي.  الأدوات المستعملـــة: اعتمدنا في دراستنا على استمارة استبيان.  النتائج المتـوصل إلـيها: لقد تم التوصل إلى النتائج التالية: − تستخدم نوادي كرة القدم الإعداد النفسي للاعب في التغلب على بعض المواقف السلبية. − تستخدم نوادي كرة القدم الإعداد النفسي للاعب على الاسترخاء والهدوء عقب المسابقات. − تستخدم نوادي كرة القدم الإعداد النفسي للاعب على تنمية وتطوير صفاته الشخصية. − يتم توجيه اللاعبينمن قبل النوادي قيد الدراسة إلى جلسات تحضير نفسي قبل المباريات للتغلب على التوتر والضغوط.  إستخـلاصات واقتراحــات: − تطوير برامج تدريب نفسي متخصصة مصممة خصيصاً للفئة العمرية المحددة تستهدف تعزيز الثقة بالنفس وإدارة التوتر. − عقد ورش عمل وجلسات توعية وتثقيف للمدربين وأولياء الأمور حول أهمية التحضير النفسي وكيفية دعم اللاعبين في هذا الجانب. − تطوير برامج دعم اجتماعي للفرق الرياضية تشمل دعماً نفسياً واجتماعياً للمشاركين، بما في ذلك جلسات تحفيزية ومساعدة نفسية. ABSTRACT :  Study title: The reality of psychological preparation among the age groups from 15 to 17 years in football clubs  Study Objective: − Identify whether football clubs use the psychological preparation of the player to overcome some negative attitudes. − Determine the extent to which football clubs use the psychological preparation of the player to relax and calm down after competitions. − Demonstrate the degree to which football clubs use the psychological preparation of the player to develop and develop his personal qualities.  Hypotheses of the study: − Football clubs use the psychological preparation of the player to overcome some negative attitudes. − Football clubs use the psychological preparation of the player to relax and calm down after competitions. − Football clubs use the psychological preparation of the player to develop and develop his personal qualities.  Field Study Procedures − Sample: The study was conducted on a sample of 62 players from football clubs at the level of the state association Souk Ahras. − Timeline: The baseline study was conducted from 20/11/2023 to 10/05/2024. − Spatial scope: The study was carried out at the level of sports clubs affiliated with the State Football Association - Souk Ahras.  The method used: The descriptive survey method was used.  Tools used: In our study, we relied on a questionnaire form.  Findings: The following findings have been made: − Football clubs use the psychological preparation of the player to overcome some negative attitudes. − Football clubs use the psychological preparation of the player to relax and calm down after competitions. − Football clubs use the psychological preparation of the player to develop and develop his personal qualities. − Players are directed by the clubs under study to pre-match psychological preparation sessions to overcome stress and pressure. ❖ Conclusions and Suggestions: − Developing specialized psychological training programs tailored to the specific age group aimed at enhancing self-confidence and managing stress. − Holding workshops and awareness and education sessions for trainers and parents on the importance of psychological preparation and how to support players in this aspect. − Develop social support programs for sports teams that include psychological and social support for participants, including motivational sessions and psychological assistance. résumé :  Titre de l'étude : La réalité de la préparation psychologique chez les groupes d'âge de 15 à 17 ans dans les clubs de football.  Objectif de l'étude : − Identifiez si les clubs de football utilisent la préparation psychologique du joueur pour surmonter certaines situations négatives. - Déterminer dans quelle mesure les clubs de football utilisent la préparation psychologique pour que le joueur se détende et se calme après les compétitions. - Expliquer dans quelle mesure les clubs de football utilisent la préparation psychologique du joueur pour développer ses caractéristiques personnelles.  Hypothèses d'étude : − Les clubs de football utilisent la préparation psychologique du joueur pour surmonter certaines situations négatives. - Les clubs de football utilisent la préparation psychologique du joueur pour se détendre et se calmer après les compétitions. - Les clubs de football utilisent la préparation psychologique du joueur pour développer ses q caractéristiques personnelles.  Procédures d'étude sur le terrain - Échantillon : L'étude a été menée sur un échantillon de 62 joueurs issus des clubs de football au niveau de l'association étatique de Souk Ahras. - Portée temporelle : L'étude de base a été réalisée sur la période s'étendant du 20/01/2024 au 10/05/2024. - Portée spatiale : L'étude a été menée au niveau des clubs sportifs affiliés à la Fédération Nationale de Football - Souk Ahras.  Méthode utilisée : La méthode d'enquête descriptive a été utilisée.  Outils utilisés : Dans notre étude, nous nous sommes appuyés sur unquestionnaire.  Résultats : Les résultats suivants ont été atteints : − Les clubs de football utilisent la préparation psychologique du joueur pour surmonter certaines situations négatives. - Les clubs de football utilisent la préparation psychologique du joueur pour se détendre et se calmer après les compétitions. - Les clubs de football utilisent la préparation psychologique du joueur pour développer ses caractéristiques personnelles. - Les joueurs sont orientés par les clubs étudiés vers des séances de préparation psychologique avant les matches pour surmonter les tensions et la pression.  Conclusions et suggestions : − Développer des programmes de formation psychologique spécialisés spécifiquement conçus pour une tranche d'âge spécifique visant à renforcer la confiance en soi et à gérer le stress. − Organiser des ateliers, des séances de sensibilisation et d'éducation pour les entraîneurs et les parents sur l'importance de la préparation psychologique et sur la manière de soutenir les joueurs dans cet aspect. − Développer des programmes de soutien social pour les équipes sportives qui incluent un soutien psychologique et social pour les participants, y compris des séances de motivation et une assistance psychologique.
Keywords: التحضير النفسي; الفئات العمرية من 15 الى 17 سنة; كرة القدم; نوادي كرة القدم; Psychological preparation; age groups from 15 to 17 years; football; football clubs; Préparation psychologique; groupes d'âge de 15 à 17 ans; clubs de football.